Arti Penting Kewirausahaan dalam Meningkatkan Kreativitas Bisnis - Putri Adinda, Amelia (IKAMAS: Manajemen Pendidikan Islam, 2022)
In starting a business, economists need to be motivated or creative from a young age when running it so that later they don't feel bored or tired and are l unable to maintain entrepreneurship. Without careful research and thought, to develop creatively as an entrepreneur, and any strategy or program executed without doing so will not yield the best results. The purpose of this research is for business people to develop techniques to encourage the entrepreneurial spirit in the business environment. The analysis for this research uses the method of content analysis, descriptive analysis, research stages, and library research. The results of this study indicate a number of perception-based barriers to starting a business, such as the perception of being too old or young, not being rewarded, or lack of finances. This barrier needs to be reduced by more knowledge from young economists, which is provided through community service. The hope is that the existence of young economists who are active in the business world can inspire the public's imagination about economic innovation. In this situation, it is hoped that entrepreneurs will continue to run their business according to entrepreneur norms.